Peter van Alfen and Ute Wartenberg (eds) (with Wolfgang Fischer-Bossert, Haim Gitler, Koray Konuk, and Catharine C. Lorber), White Gold: Studies in Early Electrum Coinage - Rutter, Keith (Journal of Greek Archaeology, 2021)
The title of this book, White Gold, derives from the phrase used once by Herodotus (λευκοῦ χρυσοῦ, 1.50.2) and more frequently in inscriptions to describe electrum, an alloy of gold and silver from which the first coins in the western tradition were made. The alloy was mostly referred to as electrum (ἤλεκτρον), which could also mean ‘amber’ – the application of the word to coins derived from their colour. The origin of the book goes back to a spectacular exhibition held in 2011 at the Israel Museum, Jerusalem, in which five hundred such coins were displayed. Two conferences, held in Jerusalem (2011) and New York (2013), were convened to address the many problems presented by these coins.